Development of a Bioprocess to Improve the Phenolic Compounds Content and Antioxidant Capacity in Blue Corn Grains - Ulises Ramírez-Esparza; Andrés Javier Ordoñez-Cano; Emilio Ochoa-Reyes; Fernando Méndez-González; Ramiro Baeza-Jimenez; Mónica Alvarado-González; Juan A. Ascacio-Valdes; José Juan Buenrostro-Figueroa (Fermentation)
Corn, a widely cultivated cereal, is a rich source of several antioxidant compounds, including phenolic compounds. Some of these compounds are bound within the components of the corn cell wall, requiring specific treatments to release them. Solid-state fermentation (SSF) using Rhizopus oryzae enhanced the antioxidant capacity and phenolic content in legumes and grains. However, there is limited information regarding its application in blue corn. This study aimed to evaluate the effect of R. oryzae growth on the phenolic content and antioxidant capacity of blue corn kernels. The results demonstrated that R. oryzae used blue corn kernels for growth, which led to an increase in free phenolic compounds, reaching their highest concentration at 60 h of culture. Compared to the unfermented control (0 h), SSF increased by up to 161% in total phenolic content and a 94% increase in antioxidant capacity. The main phenolic compounds identified in the blue corn extracts at 60 h using RP-HPLC-ESI-MS included caffeic acid 4-O-glucoside, rosmanol, p-coumaroyl tartaric acid glucosidic ester, 5-heptadecylresorcinol, and caffeoyl tartaric acid. The SSF represents an eco-friendly method for enhancing the antioxidant capacity and phenolic compounds of blue corn grain.